The Mechanism Through Which Corporate Social Responsibility (CSR) Affects Customer Patronage of Manufacturing Companies: Modeling the Mediating Role of Corporate Reputation and the Moderating Role of Customer Awareness of CSR Activities - Ruijie Shu; Hua Xia; Oberiri Destiny Apuke (SAGE Open)
Despite the growing body of studies exploring the effect of corporate social responsibility (CSR) on business outcomes, there is still limited understanding of the mechanism through which CSR activities affect customer patronage (CP). This study modeled the mediating role of corporate reputation (CR) in the relationship between CSR activities and customer patronage (CP). The study further tested the moderating role of customer awareness. Data was drawn from 1,200 customers of a manufacturing company using Qualtrics online crowdsourcing company. A structural equation modeling (SEM) was used to actualize this study. We found that a company’s CSR activities promote CR. Specifically, community development and philanthropic responsibilities have more impact in promoting the CR of a company. CR was found to mediate the relationship between CSR activities and CP. Finally, consumer awareness (CA) of CSR activities moderates and increases the correlation between CR and CP.